A multidimensional physical scale is a useful screening test for mild depression associated with childcare in Japanese child-rearing women - Takeuchi, Mariko; Matsunaga, Michiko; Egashira, Ryuichiro; Miyake, Akimitsu; Yasuno, Fumihiko; Nakano, Mai; Moriguchi, Misaki; Tonari, Satoko; Hotta, Sayaka; Hayashi, Haruka; Saito, Hitomi; Myowa, Masako; et al. (Frontiers in Psychiatry, 2022)
Maternal depression is one of the important problems of postpartum women. For its early detection and appropriate treatment, it is necessary to identify women at high risk for depression quickly and easily. A simple screening scale for depression from physical aspects, the Multidimensional Physical Scale (MDPS), which is a 17-item, self-report, three-step scale (0,1, 2) according to the theory of Kampo medicine, was developed. The aim of the present study was to develop (n=785) and validate (n=350) the MDPS that was designed to rate the risk of depression. The Beck Depression Inventory - Second Edition was used for determination of depression. In the development cohort, the final model was determined using multi-regression logistic analysis. The components of the MDPS for mothers (MDPS-M) were developed, containing the total score of MDPS (0-34 points) and resumption of menstruation or not (-3, 0 points). Receiver-operating characteristic curve analysis of the MDPS-M (-3 – 34) for identifying a high risk of depression showed moderately good discrimination (area under the curve (AUC) = 0.74, 95% confidence interval (CI): 0.70-0.78). At the cutoff value of MDPS-M (9/10), its sensitivity, specificity, positive predictive value, and negative predictive value were 84.9%, 45.7%, 36.7%, and 89.2%, respectively. External validation of the MDPS-M showed moderately good discrimination (AUC=0.74, 95% CI: 0.68-0.79) using the same analysis as the development cohort. These results indicate that the MDPS-M is a useful, simple, clinical scale for early identification of mothers at high risk of depression in primary care.